Paradigma Hubungan antara Kekuasaan Negara dan Perlindungan HAM Di Indonesia - Sri Hastuti Puspitasari (Fakultas Hukum Universitas Islam Indonesia, 2003)
In fact, the existence of changes on the rules of Human Right at constitution 1945 get a proper moment because, at that time, Indonesia have fundamental changes from the authotarian regime to democratic regime andin general, the states In being fundamental changes in their state life is followed by the constitutional changes. But the changes of the constitution would be meaningful if it is followed by the commitment all parties in enforcing the Human Right, and the beginning is on the legislative organ who has responsible to respond the problem of Human Right by creating legal instrument for Human Right protection.